The Old Testament speaks ; v. 8 God's Word for a former generation explained for today's people - Fleming, Donald C. (Kowloon, Hong Kong Living Books for All, 1982)
Contents : v. 8 : Jeremiah, Lamentations.
Brethren writer. Donated by the author.
Keywords: Bible. O.T. -- introductions